2021
DOI: 10.1093/pm/pnab140
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy, Adverse Events, and Withdrawal Rates of the Pharmacological Management of Chronic Spinal Cord Injury Pain: A Systematic Review and Meta-Analysis

Abstract: Objective To establish the efficacy of medications, incidence of adverse events (AE) and withdrawal rates (WR) of the pharmacological management of chronic spinal cord injury (SCI) pain. Methodology PubMed, MEDLINE, Embase, CINAHL, Web of Science, CENTRAL and PsycINFO were searched (November 2017) and updated (January 2020). Two independent review authors screened and identified papers for inclusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Sensitivity analysis was conducted by excluding studies rated as high risk of bias, excluding a trial of Namisol ®38 (purified plant-based dronabinol) that was grouped with synthetic dronabinol, and by repeating analyses using a random effects model based on the profile likelihood method with the Bartlett's correction to reduce potential deviation from the null distribution when the number of studies is small. 39 All meta-analyses were conducted using command metan and admetan in Stata/SE 16.1 (StataCorp, College Station, TX). Publication bias (small study effect) was assessed using both funnel plots and the Egger test when there were eight or more studies included in a meta-analysis.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Sensitivity analysis was conducted by excluding studies rated as high risk of bias, excluding a trial of Namisol ®38 (purified plant-based dronabinol) that was grouped with synthetic dronabinol, and by repeating analyses using a random effects model based on the profile likelihood method with the Bartlett's correction to reduce potential deviation from the null distribution when the number of studies is small. 39 All meta-analyses were conducted using command metan and admetan in Stata/SE 16.1 (StataCorp, College Station, TX). Publication bias (small study effect) was assessed using both funnel plots and the Egger test when there were eight or more studies included in a meta-analysis.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Advances in research and technology have provided optimism for SCI patients in terms of motor and sensory recovery 2 . However, studies have shown 61% of patients with SCI experience debilitating chronic pain that affects mood, functioning, and quality of life 3 . Improving the management of pain is a top priority for these SCI patients over research in other neurological deficits like paraplegia.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the management of pain is a top priority for these SCI patients over research in other neurological deficits like paraplegia. The pain associated with SCI can be divided into nociceptive pain, neuropathic pain (NP), other pain, or unknown pain 3 . Nociceptive pain arises from musculoskeletal structures and viscera, while NP can be due to incorrect transmission because of the spinal cord and nerve damage 4 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations